014 Atorvastatin protects human myocardium from lethal ischaemia-reperfusion injury by activating the risk pathway. (22nd September 2015) - Rees, P S C; Babu, G G; Boston-Griffiths, E A; Bognolo, G; Hayward, M; Kolvekar, S; Lawrence, D; Yap, J; Hausenloy, D J; Yellon, D M
Abstract : Background: Previous animal studies have demonstrated that acute treatment with atorvastatin at reperfusion reduces myocardial infarct size by up-regulating the Akt and Erk1/2 components of the Reperfusion Injury Salvage Kinase (RISK) pathway. Whether this cardioprotective strategy applies to human cardiac tissue is unknown. Objective: To determine whether atorvastatin, administered at reperfusion, protects human atrial tissue from ischaemia-reperfusion injury (IRI) via activation of the RISK pathway. Methods: Local UCLH/UCL Ethical Committee approval was granted. Human atrial trabeculae were isolated from right atrial appendage tissue harvested from consenting adult patients undergoing elective cardiac surgery. The atrial trabeculae were subjected to 90 min of hypoxia followed by 120 min reoxygenation as simulated ischaemia-reperfusion injury. Following this, recovery of contractile function was determined and compared to baseline. Atrial trabeculae were randomised to the following groups: 1. Control (N=14); 2. Hypoxic preconditioning positive control (N=4); 3. Atorvastatin (25 μM) at reperfusion (N=9); 4. Atorvastatin plus UO126 (10 μM), a MEK1/2-Erk1/2 inhibitor (N=4); 5. Atorvastatin plus LY294002 (15 μM), a PI3K-Akt inhibitor (N=4); 6. Atorvastatin plus L-NAME (100 μM), a non-specific nitric oxide synthase inhibitor (N=7); 7. Atorvastatin plus 1400W (5μM), a specific inducible nitric oxide synthase inhibitor (N=5); 8. Inhibitor-only controls (N=18). Results: Control atrial trabeculae recovered 37.5±1.6% of baseline contractile function following simulated IRI. Treatment with atorvastatin 25 μM at reperfusion significantly improved the recovery of contractile function (61.1±3.8%, p<0.001), an effect which was abolished by LY294002 (29.88±2.3%), UO126 (45.0±3.8%), L-NAME (34.35±4.0%) and 1400 w (38.57±5.0%). Conclusions: Atorvastatin, administered at reperfusion, protects human atrial muscle from simulated IRI via activation of the Akt and Erk1/2 components of the RISK pathway and nitric oxide synthase.